Association between urinary nickel with obesity status in adults: A cross-sectional study - Wang, Gao-Xiang; Huang, Bao-Li; Li, Jun-Tong; Fang, Ze-Bin; Feng, Le-Yi; Zhao, Heng-Xia; Chu, Shu-Fang; Liu, De-Liang; Li, Hui-Lin (Frontiers in Public Health, 2023)
Objectives: The prevalence of obesity is on the rise and is connected to numerous factors. However, the relationship between obesity and nickel has never been investigated. Our study aimed to explore the association between urinary nickel and obesity Status in adults. Methods: From the 2017–2018 National Health and Nutrition Examination Surveys (NHANES), 1705 participants greater than or equal to 18 years of age were enrolled. To explore further the relationship among urinary nickel, body mass index (BMI), and waist circumference(WC), Weighted multivariate linear regression analyses and further subgroup analyzes were conducted. Results: Urinary nickel does not correlate with BMI level but positively correlates with WC. In the subgroup analyzed according to sex, Urinary nickel has a positive correlation with BMI and WC in males but has a negative correlation in females. Secondary stratification analysis according to sex and race, Urinary nickel positively correlates with BMI in White males. It also positively correlates with WC in both White and Black males. Conclusions: A correlation was found between urinary nickel levels and BMI and WC in adult males. Adult men, especially those already obese, may need to reduce nickel exposure.